2018
DOI: 10.1109/tnsre.2018.2881606
|View full text |Cite
|
Sign up to set email alerts
|

Noise-Assisted Multivariate EMD-Based Mean-Phase Coherence Analysis to Evaluate Phase-Synchrony Dynamics in Epilepsy Patients

Abstract: Spatiotemporal evolution of synchrony dynamics among neuronal populations plays an important role in decoding complicated brain function in normal cognitive processing as well as during pathological conditions such as epileptic seizures. In this paper, a non-linear analytical methodology is proposed to quantitatively evaluate the phase-synchrony dynamics in epilepsy patients. A set of finite neuronal oscillators was adaptively extracted from a multi-channel electrocorticographic (ECoG) dataset utilizing noise-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…The EMD and instantaneous frequency analysis are a promising tool for neuroscience and electrophysiology (12). The EMD has successfully been applied to electrophysiology data in a range of contexts including (but not limited to) rodent hippocampal theta oscillations (20), epileptic activity in human patients (21), TMS evoked EEG responses (22) and for assessing instantaneous phase-synchrony in intracranial EEG (23). We build on this prior work to introduce phase-aligned instantaneous frequency as a general measure of oscillatory waveform shape.…”
Section: : Introductionmentioning
confidence: 99%
“…The EMD and instantaneous frequency analysis are a promising tool for neuroscience and electrophysiology (12). The EMD has successfully been applied to electrophysiology data in a range of contexts including (but not limited to) rodent hippocampal theta oscillations (20), epileptic activity in human patients (21), TMS evoked EEG responses (22) and for assessing instantaneous phase-synchrony in intracranial EEG (23). We build on this prior work to introduce phase-aligned instantaneous frequency as a general measure of oscillatory waveform shape.…”
Section: : Introductionmentioning
confidence: 99%
“…Computational modeling was described in our previous study to quantify and compare meanλ 1:60% value among three epileptic networks with different phase-synchrony level [27]. Simulation results demonstrated that as the phase-synchrony level increases between neuronal oscillators from its minimum to its maximum, the meanλ 1:60% value decreases accordingly.…”
Section: Dataset and Methodsmentioning
confidence: 99%
“…Furthermore, the normalized meanλ 1:60% values were measured to quantify phase-synchrony levels as seizures evolve in order to magnify the small relative changes of the meanλ 1:60% over time. It should be noted that phase-synchrony was observed to increase from mid-ictal towards seizure end and achieved its maximum level at seizure termination in all of the analyzed epilepsy patients [27].…”
Section: Dataset and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, its de-noising ability depends on the selection of wavelet base function and the determination of threshold. Empirical Mode Decomposition (EMD) based de-noising method [11]- [13] applies EMD to decompose time series to multiple Intrinsic Mode Functions (IMFs) and a Residue (R). As the noise is concentrated in the high-frequency IMFs, only the noise reduction of the high-frequency IMFs is required.…”
Section: Introductionmentioning
confidence: 99%